Comparative Response to Printed and Digital Format Poetry: A Case Study of Ubaidil’s Poem Sarmin dan Kampung Masa Kecilnya - Iskarna, Tatang (English Language and Literature International Conference (ELLiC) Proceedings, 2024)
This study compares readers' responses to printed and digital poetry, focusing on video poetry Sarmin dan Kampung Masa Kecilnya written by Ade Ubaidil to understand how different presentation mediums impact engagement, interpretation, and emotional connection to poetry. With advancing technology challenging print media, questions arise about how format influences literary works, particularly poetry. Authors, publishers, and educators must adapt to changing reading habits and preferences by understanding reader responses to printed and digital media. Employing qualitative methods, the study conducts a survey, focus group discussions, and in-depth interviews to explore participants' experiences, preferences, and perspectives. The survey measures emotional involvement; explores mood, atmosphere, message understanding, and multimedia influence; and examines the preferences concerning memory recall and authorship authenticity perceptions. Of the 65 students surveyed, preferences differed when asked directly about reading the poem Sarmin dan Kampung Masa Kecilnya, with 40 preferring digital, 23 printed, and 2 both. Digital formats showed mixed effects on reader engagement, emotional response, and comprehension. While digital readers demonstrated higher interest, emotional response, and mood understanding, they showed less understanding of tone and storyline compared to print readers. Multimedia was largely viewed as beneficial. Digital formats exhibited better memory recall but raised more concerns about authenticity, with more students trusting printed materials. Recommendations varied, with 30 students preferring digital, 22 printed, 6 both, and 7 suggesting format depending on the reader and text. These findings underscore the complex relationship between format choices, reader engagement, and perceptions of authenticity in contemporary literature consumption. Flexibility and consideration of individual tastes and literary content are emphasized for adapting to evolving preferences